Uwarunkowania pokoju w refleksji Jana Pawła II - Bochenek, Krzysztof (Przegla̜d religioznawczy, 2015)
Although the peace at the beginning of the twenty-first century seems to be a value most desired by humanity, this is its achievement that seems to be impossible. Presenting his own vision of peace, John Paul II refered to personalism, which protects the dignity of all, with no exception, the human person. The peace comes to respect for inviolable human rights, with the right to life at the forefront. Other considerations of peace is: social justice, intercultural and interreligious dialogue, concern for the education of the next generations, building a civilization of brotherhood, forgiveness and love.